A Set of Reliable Samples for the Study of Biomarkers for the Early Diagnosis of Parkinson's Disease - Konjevod, Marcela; Sáiz, Jorge; Barbas, Coral; Bergareche, Alberto; Ardanaz, Eva; Huerta, José Ma; Vinagre-Aragón, Ana; Erro, Ma Elena; Chirlaque, Ma Dolores; Abilleira, Eunate; Ibarluzea, Jesús Ma; Amiano, Pilar (Frontiers in Neurology, 2022)
Background: Parkinson’s disease (PD) is a progressive neurodegenerative disorder, diagnosed according to the clinical criteria that occur in already advanced stages of PD. Therefore, the definition of biomarkers for the early diagnosis of Parkinson’s disease is a challenge that might improve treatment and avoid complications in this disease. We propose a set of reliable samples for the identification of reliable biomarkers for the early diagnosis of PD. Methods: Case-control study included plasma samples from the Spanish EPIC-Navarra cohort, part of the EPIC-Spain study. All the case samples were provided by healthy volunteers who were followed up for 15.9 (± 4.1) years and developed PD disease later on, after the sample collection. An analytical multiplatform based on liquid chromatography and tandem mass spectrometry was used for the analysis of samples. Results: Out of 40 analytes that were selected and studied due to their involvement in established cases of PD, seven significantly different metabolites between PD cases and healthy control subjects were obtained in this study (benzoic acid, palmitic acid, oleic acid, stearic acid, myo-inositol, sorbitol and quinolinic acid). These metabolites are related to mitochondrial dysfunction, the oxidative stress and the mechanisms of energy production. Conclusions: We propose the samples from the EPIC study as reliable and invaluable samples for the search of early biomarkers of PD. Likewise, this study might also be a starting point in the establishment of a well-founded panel of metabolites that can be used for the early detection of this disease.